La clausura en el régimen tributario, y su afectación al Derecho Constitucional al trabajo de los grupos vulnerables - Aguilar Álvarez, Jessica Nohely (2016)
This thesis entitled: "The closure in the tax regime, and its effect to the constitutional right to work of vulnerable groups, is the product of a careful analysis of the Constitution of the Republic of Ecuador where we found that guarantees human rights for all people; providing a privilege to individuals who belong to the group of priority such as the elderly, disabled, suffering from catastrophic illnesses, pregnant women, among others, being these that has been dedicated research to be vulnerable to the rest of people. The rights of these people enjoy is health, food, exemption from payment of taxes, the right to work, among other rights. The state through its agencies collecting taxes, such as the Internal Revenue Service controls that all people with economic activity comply with their tax obligations, otherwise proceed to punish taxpayers shutting down their businesses, without considering that in some cases the owners are people who belong to the group of priority attention and that their premises are the only means of subsistence to cover their basic needs, however, the tax legislation does not provide, nor does it measure these consequences and proceed to close these businesses by not issuing sales receipts, violating the right to work of these people and inobservándose the constitutional rule of law which provides for the Constitution, becoming a need to conduct a thorough study of this issue that generates violation of rights of people focus group.